Potential for plant biocontrol activity of isolated Pseudomonas aeruginosa and Bacillus stratosphericus strains against bacterial pathogens acting through both induced plant resistance and direct antagonism. Issue 23 (24th October 2017) - Durairaj, Kaliannan; Velmurugan, Palanivel; Park, Jung-Hee; Chang, Woo-Suk; Park, Yool-Jin; Senthilkumar, Palaninaicker; Choi, Kyung-Min; Lee, Jeong-Ho; Oh, Byung-Taek
Abstract: Phytopathogenic bacteria have caused significant damage to agricultural crops in both controlled and open cultivation practices, imposing heavy losses to farmers. Thereby, the goal of this study was to evaluate Pseudomonas aeruginosa and Bacillus stratosphericus isolated from soil has antagonistic activity against bacterial phytopathogens with the potential to control plant diseases. Isolated novel strains of P. aeruginosa and B. stratosphericus showed broad spectrum of antagonistic activity against five bacterial phytopathogens. Antagonistic activity was examined under optimized pH (8 and 7), carbon sources (lactose and starch), nitrogen sources (ammonium chloride, peptone and ammonium nitrate) for P. aeruginosa and B. stratosphericus, respectively, and biocatalyst production (chitinase, protease and amylase) was studied. Additionally, up-regulation of defense-related genes (PR-1a and PAL) was studied in tomato plants treated with P. aeruginosa and B. stratosphericus . The induction of defense-related genes in tomato plant was triggered after 12 h treatment with a cell concentration of 0.20 O.D. for P. aeruginosa and 0.21 O.D. for B. stratosphericus during treatment period. Broad spectrum antagonistic activity was observed due to antibiotic and siderophore production by P. aeruginosa and B. stratosphericus . Abstract : The antagonistic activity of P. aeruginosa and B. stratosphericus suggests their potential application as promising bio-control agents for controlling bacterial pathogens of agricultural plants.